2019
DOI: 10.1155/2019/3989304
|View full text |Cite
|
Sign up to set email alerts
|

Multiannual, Intensive Strength-Endurance Training Modulates the Activity of the Cardiovascular and Autonomic Nervous System among Rowers of the International Level

Abstract: Introduction Professional athlete training is significantly different from recreational physical activity, and sustained, repetitive exposure to over-strenuous and intensive training may result in critical changes of most systems and organs in a sportsman's body. Aim The assessment of the influence of multiannual strength-endurance training on the autonomic nervous system (ANS) and cardiovascular system (CVS) among the rowers of Polish national team. Materials and Methods 20 rowers, aged 20–30, seniors of Poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In fact, competitive rowers in our study reported lower AIx75, an consequently lower arterial stiffness, compared to recreational athletes ( Figure 4 ). These findings are in accordance with research conducted in adults which reports a significant increase in peripheral artery diameters and baroreflex sensitivity, and a decrease in vascular peripheral resistance in rowers compared to a non-athletic group ( 5 , 7 , 8 ). However, another study reported higher AIx in adult rowers compared to a control group underlining the need of additional investigations in this specific topic ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, competitive rowers in our study reported lower AIx75, an consequently lower arterial stiffness, compared to recreational athletes ( Figure 4 ). These findings are in accordance with research conducted in adults which reports a significant increase in peripheral artery diameters and baroreflex sensitivity, and a decrease in vascular peripheral resistance in rowers compared to a non-athletic group ( 5 , 7 , 8 ). However, another study reported higher AIx in adult rowers compared to a control group underlining the need of additional investigations in this specific topic ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…Research has shown that the cardiovascular system of this type of athletes may Abbreviations AIx, Augmentation index; APP, aortic pulse pressures; BDBP, brachial diastolic blood pressure; BMI, body mass index; BPP, brachial pulse pressures; BSBP, brachial systolic blood pressure; CR, competitive rowers; HPV, height at peak velocity; HR, heart rate; EDms, ejection duration in ms; FM, fat mass; FFM, fat free mass; MAP, mean aortic pressure; MBP, mean brachial pressure; ORS, other recreational sports; RER, respiratory exchange ratio; RHR, resting heart rate; RR, recreational rowers; PWV, pulse wave velocity; SEVR, subendocardial viability ratio; VO 2 Peak, oxygen consumption in absolute terms at exercise peak. undergo significant remodelling changing both the structure and function of heart and arteries (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These kinds of sports include academic rowing. In this sport, for the rational planning and control of physical fitness, it is necessary to determine the level of functional status of the above systems [15][16][17][18][19]. According to scientists, the practical solution of the problem outlined is the most possible due to the search for new ways to increase the physical preparedness of rowers in different periods of the annual cycle [20][21][22][23].…”
mentioning
confidence: 99%